CIAT in Ethiopia: Science for Impact - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2017)
CIAT has worked in Ethiopia for 30 years, in collaboration with the Ethiopian Institute of Agricultural Research (EIAR) and regional agricultural research centers. Initially focused on bean variety development − getting improved, better beans to communities, improving their nutrition and incomes − our work has broadened to include soil fertility management, sustainable land management, climate change and climate information services.